2006
DOI: 10.1007/s10397-006-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis of the round ligament revealed by an intermittent hernia

Abstract: Endometriosis is a common gynaecological pathology with pelvic and extra-pelvic localisations. We report a case of endometriosis of the round ligament revealed by an intermittent hernia. The endometriosis of the round ligament is unusual and the diagnosis may be difficult. The appearance of a roundish lump in the inguinal region associated with pain in relation to the menstrual cycle must raise the suspicion of endometriosis among the possible diagnosis. Ultrasonography and magnetic resonance imaging are the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is imperative to perform complete excision in extrapelvic endometriosis with wide surgical margins to prevent recurrence and for complete tissue diagnosis. 9,12 In case 1, wide local excision with a 1 cm margin was done for this purpose. Nonetheless, case 1 was already being diagnosed pre-operatively through FNAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to perform complete excision in extrapelvic endometriosis with wide surgical margins to prevent recurrence and for complete tissue diagnosis. 9,12 In case 1, wide local excision with a 1 cm margin was done for this purpose. Nonetheless, case 1 was already being diagnosed pre-operatively through FNAC.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons often use FNAC to aid in the diagnosis. FNAC is a quick, cost-effective, and accurate diagnostic tool to include in patients' management 12 however FNAC may cause new endometriotic implants to develop at the puncture site. 14 Direct extension of endometrial tissue along the round ligament has been suggested as the possible pathogenesis of inguinal endometriosis while iatrogenic mechanical transplantations on incision scars during surgeries are the most accepted pathogenesis for abdominal wall endometriosis.…”
Section: Discussionmentioning
confidence: 99%